(untitled) (Journal of the College of Education for Women, 2019)
For cleaner air and unpolluted continue assessment study air pollution the city ofBaghdad by measuring the concentrations of air pollutants, which included TSP, Pb, wherethe adoption of three stations (Andalus Square, Jadiriya, Allawi) are distributed in the city ofBaghdad in order to compare the concentrations of these pollutants with previous studies.Study pointed out that the city’s air contaminant, especially in minutes outstanding afterdeducting the amount of atmospheric dust thick mechanism city this year where the highestconcentration of minutes outstanding (9895) micrograms / m 3 at the station Alawi and lowerconcentration of 157 micrograms / m 3 at the station Alawi and this was higher than thedeterminants National (350) micrograms / m 3 and global amounting to 150 micrograms / m 3for a period of exposure (24 hours and one hour, respectively).The lower concentration (0.04)mcg / m 3 in Jadriya station. Summarizing the study, said the city’s air pollutant and is due toincreased traffic congestion and fuel sarong and large quantities of fuel consumed in theproduction of electric power stations and to divorced laboratories and factories governmentalorganizations and the private sector deployed in the city.